Acclimatization of in vitro seedling and clonal lycium barbarum L. (GOJI) / Nur Hanis Atikah Mat Yusoff - Mat Yusoff, Nur Hanis Atikah (2016)
Lycium barbarum L. (Goji) or known as superfood is a type of plant species with high medicinal values and high antioxidant properties which derives from Solanaceae family and native to some areas of China and Himalayan areas. Clonal propagation and subsequent acclimatization of elite in vitro seedling and clonal goji using different types of planting media has been carried out. Five different planting media were being tested and the result revealed that sterilized sand, soil, and perlite (1:1:1), sterilized peat moss and perlite (1:1), sterilized soil and perlite (1:1) sterilized sand and vermiculite (1:1) and sterilized soil, sand, topsoil (3:2:1) as control was successfully achieved as selected planting media with the aim of producing goji tea and berries. In vitro regeneration of goji showed the best performance by using MS media added with 0.3 mg/L of BAP used gelrite as solidifying agar. The best planting media for acclimatization of seedling using sterilized peat moss and perlite (1:1) with the plant height of 18.83 ± 0.48 cm and the number of leaves of 35.00 ± 0.97, while for clonal using sterilized peat moss and perlite (1:1) with the plant height of 22.67 ± 0.33 cm and the number of leaves of 48.00 ± 0.58. Thus, the successful acclimatization for both seedling and clonal of goji were identified in the greenhouse using peat moss and perlite added with compost.